Protocol for the evaluation of the population-level impact of Zimbabwe's prevention of mother-to-child HIV transmission program option B+: a community based serial cross-sectional study - Aybuke Koyuncu; Mi-Suk Kang Dufour; Sandra Irene McCoy; Sergio Bautista-Arredondo; Raluca Buzdugan; Constancia Watadzaushe; Jeffrey Dirawo; Angela Mushavi; Agnes Mahomva; Frances Cowan; Nancy Padian (BMC, 2019)
Abstract Background WHO recommends that HIV infected women receive antiretroviral therapy (ART) minimally during pregnancy and breastfeeding ("Option B"), or ideally throughout their lives regardless of clinical stage ("Option B+") (Coovadia et al., Lancet 379:221-228, 2012). Although these recommendations were based on clinical trials demonstrating the efficacy of ART during pregnancy and breastfeeding, the population-level effectiveness of Option B+ is unknown, as are retention on ART beyond the immediate post-partum period, and the relative impact and cost-effectiveness of Option B+ compared to Option A (Centers for Disease Control and Prevention, Morb Mortal Wkly Rep 62:148-151, 2013; Ahmed et al., Curr Opin HIV AIDS 8:473-488, 2013). To address these issues, we conducted an impact evaluation of Zimbabwe's prevention of mother to child transmission programme conducted between 2011 and 2018 using serial, community-based cross-sectional serosurveys, which spanned changes in WHO recommendations. Here we describe the rationale for the design and analysis. Methods/design Our method is to survey mother-infant pairs residing in the catchment areas of 157 health facilities randomly selected from 5 of 10 provinces in Zimbabwe. We collect questionnaires, blood samples from mothers and babies for HIV antibody and viral load testing, and verbal autopsies for deceased mothers/babies. Using this approach, we collected data from two previous time points: 2012 (pre-Option A standard of care), 2014 (post-Option A / pre-Option B+) and will collect a third round of data in 2017-18 (post Option B+ implementation) to monitor population-level trends in mother-to-child transmission of HIV (MTCT) and HIV-free infant survival. In addition, we will collect detailed information on facility level factors that may influence service delivery and costs. Discussion Although the efficacy of antiretroviral therapy (ART) during pregnancy and breastfeeding for prevention of mother-to-child transmission of HIV (PMTCT) has been well-documented in randomized trials, little evidence exists on the population-level impact and cost-effectiveness of Option B+ or the influence of the facility on implementation (Siegfried et al., Cochrane Libr 7:CD003510, 2017). This study will provide essential data on these gaps and will provide estimates on retention in care among Option B+ clients after the breastfeeding period. Trial registration NCT03388398 Retrospectively registered January 3, 2018.